2018
DOI: 10.1039/c8ra04074e
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging and degradation mechanism of LiFePO4/graphite batteries cycled at high discharge rates

Abstract: The effects of discharge rates (0.5C, 1.0C, 2.0C, 3.0C, 4.0C and 5.0C) on the aging of LiFePO 4 /graphite full cells are researched by disassembling the fresh and aged full cells. The capacity degradation mechanism is analyzed via electrochemical performance, surface morphologies and compositions, and the structure of the anode and cathode electrodes. The capacity fade is accelerated with increasing discharge rates. The irreversible loss of active lithium due to the generation of an SEI film is the primary agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Many studies have shown that a higher discharge rate can accelerate battery aging [28][29][30]. Several hypotheses have been made to explain this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that a higher discharge rate can accelerate battery aging [28][29][30]. Several hypotheses have been made to explain this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…However, it will decrease with the cycle numbers rising, that is, battery aging effects. For example, the battery capacity will drop down, internal resistance will increase and the chemical reaction rate will become slow . Such consequences caused by aging process of batteries are the main reason for the drop of operating performance of large pored electrical machines and limit the development of equipment which applies batteries as the energy storage system.…”
Section: Introductionmentioning
confidence: 99%
“…), some researches claim that the change of internal structure is a vital factor leads to the variety of batteries capacity . In Chikashi et al's research, the deposition of solid electrolyte interphase (SEI) on electrodes surface declines the capacity and cyclic performance of lithium‐ion batteries . Alex et al and Vadim et al studies indicate that the decomposition of electrolytes accelerates the aging process of lithium‐ion batteries owing to the falling number of active substances in electrolytes .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations